Motivational Dimensions in Second Language Acquisition: A Bibliometric Analysis of Research Trends and Thematic Evolution - Nila Umi Salamah; Aura Bunga Tauhid; Nur Hidayanto Pancoro Setyo Putro (JOLLT Journal of Languages and Language Teaching, 2026)
Motivation has long been recognized as a central determinant of success in second language acquisition (SLA); however, the development of motivation research over the last decade has not been comprehensively mapped. This study aims to examine publication trends, geographical distribution, thematic structure, and the conceptual evolution of research on motivation in second language learning through a bibliometric approach. Data were retrieved from the Scopus database for a ten-year period and analyzed using Biblioshiny and VOSviewer. These tools were employed to identify patterns of scientific productivity, country-level contributions, keyword co-occurrence, thematic clusters, and the evolution of dominant research themes. The findings reveal a steady increase in publications, indicating sustained scholarly attention to motivation in SLA. China emerged as the most productive country, followed by other major contributors from North America, Europe, the Middle East, and Asia. The keyword and thematic analyses show that current research is strongly centered on the L2 Motivational Self System, self-regulation, digital learning, learner engagement, anxiety, self-efficacy, and willingness to communicate. The thematic evolution further indicates a shift from attitude-based and static models of motivation toward more dynamic, contextual, and learner-centered frameworks that emphasize learning experiences, emotional factors, technological environments, and individual differences. This study contributes to the field by offering a systematic conceptual map of SLA motivation research and by identifying emerging directions for future inquiry. It recommends further longitudinal, cross-cultural, and technology-integrated studies to deepen understanding of how motivation develops across diverse second language learning contexts and across different stages of learner development over time.